Cvill6 and Cvill7: Potent and Selective Peptide Blockers of Kv1.2 Ion Channel Isolated from Mexican Scorpion Centruroides villegasi - Kashmala Shakeel; Muhammad Umair Naseem; Timoteo Olamendi-Portugal; Fernando Z. Zamudio; Lourival Domingos Possani; Gyorgy Panyi (Toxins, 2025)
Scorpion venoms are a rich source of peptides that modulate the activity of ion channels and can serve as a new drug for channelopathies. Cvill6 and Cvill7 are two new peptides isolated from the venom of Centruroides villegasi with MW of 4277 Da and 4287 Da and they consist of 38 and 39 amino acids, respectively, including six cysteines. Sequence alignment revealed high similarity with members of the α-KTx2 subfamily of potassium channel toxins. In electrophysiology, Cvill7 potently inhibited Kv1.2 ion channels with an IC50 of 16 pM and Kv1.3 with an IC50 of 7.2 nM. In addition, it exhibited partial activity on KCa3.1 and Kv1.1, with ~16% and ~34% inhibition at 100 nM, respectively. In contrast, Cvill6 blocked Kv1.2 with low affinity (IC50 of 3.9 nM) and showed modest inhibition of Kv1.3 (~11%) and KCa3.1 (~27%) at 100 nM concentration. Neither peptide showed any activity against other K+ channels tested in this study (Kv1.5, Kv11.1, KCa1.1, and KCa2.2). Notably, Cvill7 has a remarkable affinity for Kv1.2 and high selectivity of 450-fold over Kv1.3 and 12,000-fold over Kv1.1. These pharmacological properties make Cvill7 a potential candidate to target Kv1.2 gain of function (GOF)-related channelopathies such as epilepsy.